Perbandingan Model Pembelajaran Kooperatif Tipe Gallery Walk Dengan Tipe Learning Together Pada Aktivitas Belajar Peserta Didik Di SMA Tri Dharma Palembang - Rendika Vhalery (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
The aim of this research is 1) implements the learning model with gallery walk type in student learning activities, 2) implements the cooperative learning model with learning together type in student learning activities, 3) compare the gallery walk type of cooperative learning with learning together type in student learning activities. The type of this research is experimental and comparative. Population in this research is student of Tri Dharma Palembang senior high school. The research sample is XI Social 1 as the Experiment Class 1 and XI Social 2 as the Experiment Class 2. The result shows 1) there is an impact from the implementation of gallery walk type of cooperative learning in students learning activities, 2) there is an impact of implementation of learning together type in student learning activities, 3) there is a comparison of cooperative learning of gallery walk type and learning together type in students learning activities.